Gut microbiota and kidney function in autosomal dominant polycystic kidney disease participants in Cameroon: a cross-sectional study - Inès Obolo Nwaga; Victorine Bandolo Nzana; Rhoda Nsen Bughe; Isaac Dah; Cheboh Cho-Fon; Maimouna Mahamat; Emmanuelle Ndjong; Aristide Nono; Jean Claude Mballa; Fon Abongwa Acho; Vicky Ama Moor; Wilfred Fon Mbacham; et al. (BMC Nephrology)
Abstract Background and hypothesis Gut dysbiosis characterized by an imbalance in pathobionts (Enterobacter, Escherichia and Salmonella) and symbionts (Bifidobacterium, Lactobacillus and Prevotella) can occur during chronic kidney disease (CKD) progression. We evaluated the associations between representative symbionts (Bifidobacterium and Lactobacillus) and pathobionts (Enterobacteriaceae) with kidney function in persons with autosomal dominant polycystic kidney disease (ADPKD). Methods In this cross-sectional study, 29 ADPKD patients were matched to 15 controls at a 2:1 ratio. Clinical data and biological samples were collected. The estimated glomerular filtration rate (eGFR) was calculated from the serum creatinine concentration using the 2009 Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. Microbial DNA extracted from stool specimens and amplified by qPCR was used to quantify Enterobacteriaceae, Bifidobacterium and Lactobacillus abundance. Differences between ADPKD subgroups and controls were assessed using nonparametric tests. Results The mean age (SD) of the 44 participants was 40.65 (± 11.9) years. Among the participants with ADPKD, 62.1% experienced flank pain, and 48.3% had hypertension. Their median eGFR [IQR] was 74.4 [51.2–94.6] ml/min/1.73m2. All stool samples had Enterobacteriaceae. Lactobacillus abundance was lower in ADPKD participants with more pronounced kidney function decline (CKD G3-5: 0.58 ng/μL) than in those with milder damage and controls (G1-2: 0.64 ng/μL, p = 0.047; controls: 0.71 ng/μL, p = 0.043), while Enterobacteriaceae abundance was greater in ADPKD patients with lower kidney function (CKD G3-5: 78.6 ng/μL) than in those in the other two groups (G1-2: 71.6 ng/μL, p = 0.048; controls: 70.5 ng/μL, p = 0.045). Conclusion Decreased kidney function was associated with decreased symbiont and increased pathobiont abundance in ADPKD patients, suggesting a potential role for the microbiota in disease progression and possible targets for further research.